Matrix metalloproteinase 2 destabilizes Dally-like protein to restrict extracellular Wingless distribution. - Waghmare, I.; Page-McCaw, P.S.; Page-McCaw, A. (Molecular Biology of the Cell, 2025)
Cell-surface glypicans distribute several extracellular ligands, including the Wnts, which are secreted to function at short and long range in a tissue. The Drosophila glypican Dally-like protein (Dlp) interacts with Wnts to inhibit short-range Wnt signaling and promote long-range signaling by the Drosophila Wnt1, Wingless (Wg). Dlp-dependent long-range Wg distribution in the fly ovary is attenuated by metalloproteinase 2 (Mmp2). Here, we report that Mmp2 destabilizes cell-surface Dlp, causing it to be internalized. Further, after Mmp2 cleavage, Dlp sequesters more Wg, suggesting that cleaved Dlp removes Wg from the extracellular space to limit its availability for signaling. Based on these and our previous results, we propose that coordinated activities of uncleaved and cleaved Dlp regulate proper extracellular Wg distribution. Overall, this study identifies the molecular basis of protease-mediated inhibition of a cell-surface glypican to modulate ligand distribution and function.